Solar Drying Technology: Current Research Trends and Future Perspectives - Apriandi, Nanang; Raharjanti, Rani; An-nizami, Avicenna; Herlambang, Yusuf Dewantoro; Pambudi, Yoyok Dwi Setyo; Rozi, Khoiri; Negara, Komang Metty Trisna; Setyowati, Nur (LPPM Universitas Andalas, 2024)
Solar drying technology has become a vital innovation for sustainable food preservation and renewable energy utilization, offering an energy-efficient alternative to conventional drying methods. This study provides a comprehensive bibliometric analysis of research trends, influential authors, key institutions, and geographical contributions in the field of solar drying technology from 2004 to 2024. We analyzed 108 relevant publications using the Scopus database and VOSviewer software, revealing a significant increase in research output since 2010, with a marked surge after 2016. India and China emerge as leading contributors, driven by their large agricultural sectors and favorable solar conditions. Key research efforts have focused on improving energy efficiency, optimizing drying processes, and preserving product quality. Despite these advancements, critical gaps remain, particularly in scaling solar drying systems and integrating hybrid technologies that combine solar energy with other renewable sources. This study highlights the importance of interdisciplinary collaboration to advance technological innovation and address challenges in food security and energy sustainability. Future research should focus on developing hybrid systems, finding better ways to store energy, and studying how solar drying affects the taste and nutritional value of food in order to make it more useful in a wider range of climates and farming situations. Keywords: Solar Drying Technology, Bibliometric Analysis, Renewable Energy, Hybrid Systems, and Food Preservation.